2021
DOI: 10.1016/j.immuni.2021.08.025
|View full text |Cite
|
Sign up to set email alerts
|

A SARS-CoV-2 antibody broadly neutralizes SARS-related coronaviruses and variants by coordinated recognition of a virus-vulnerable site

Abstract: Potently neutralizing SARS-CoV-2 antibodies often target the spike protein receptor binding site (RBS), but the variability of RBS epitopes hampers broad neutralization of multiple sarbecoviruses and drifted viruses. Here, using humanized mice, we identified an RBS antibody with a germline V H gene that potently neutralized SARS-related coronaviruses including SARS-CoV and SARS-CoV-2 variants. X-ray crystallography revealed coordinated recognition by the heavy chain of non-RBS conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 87 publications
2
37
0
Order By: Relevance
“…Thus, it was the cumulative effect of several mutations that abrogated antiviral activity of the other monoclonal antibodies. REGN10933 (Casirivamab), the neutralizing activity of which has been previously found to be affected by E484K and K417N of the Beta spike protein, 4 , 40 , 41 is decreased another 8-fold by E484A of Omicron. REGN10987 (Imdevimab), which is nearly impervious to mutations in the earlier VOCs, was compromised by four Omicron mutations (S371L, S373P, N440K, G446S).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was the cumulative effect of several mutations that abrogated antiviral activity of the other monoclonal antibodies. REGN10933 (Casirivamab), the neutralizing activity of which has been previously found to be affected by E484K and K417N of the Beta spike protein, 4 , 40 , 41 is decreased another 8-fold by E484A of Omicron. REGN10987 (Imdevimab), which is nearly impervious to mutations in the earlier VOCs, was compromised by four Omicron mutations (S371L, S373P, N440K, G446S).…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated a possibility to develop a heterologous prime-boost vaccine strategy for a universal vaccine that can protect against a broad spectrum of SARS-related coronaviruses. A recent report also showed that in mice, sequential immunization S/RBD vaccine of SARS-CoV, SARS-CoV-2, and MERS-CoV led to induction of cross-reactive antibodies and isolation of monoclonal antibodies with broadly neutralizing activities [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For pandemic preparedness, pan-sarbecovirus therapeutics and vaccines that are effective against future SARS-CoV-2 variants and other sarbecoviruses are urgently needed 1114 . Several broad sarbecovirus neutralizing antibodies have been reported 20,2334 ; however, since the number of antibodies studied has been limited, we still lack a comprehensive understanding of the RBD epitopes that could induce broad sarbecovirus neutralizing antibodies.…”
Section: Mainmentioning
confidence: 99%